2021
DOI: 10.1021/acsami.1c20230
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Main Group Metal-Embedded Nitrogen-Doped Carbon Materials as Frustrated Lewis Pair Catalysts for CO2 Hydrogenation to Formic Acid

Abstract: Developing efficient and inexpensive main group catalysts for CO 2 conversion and utilization has attracted increasing attention, as the conversion process would be both economical and environmentally benign.Here, based on the main group element Al, we designed several heterogeneous frustrated Lewis acid/base pair (FLP) catalysts and performed extensive firstprinciples calculations for the hydrogenation of CO 2 . These catalysts,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…The carbon nitride group is another 2D material that is widely used in heterogeneous catalysis [90]. For example, Wan et al reported Al/B doping C 2 N and g-C 3 N 4 to construct FLPs from their DFT calculations [55].…”
Section: Flps Based On Functionalized Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon nitride group is another 2D material that is widely used in heterogeneous catalysis [90]. For example, Wan et al reported Al/B doping C 2 N and g-C 3 N 4 to construct FLPs from their DFT calculations [55].…”
Section: Flps Based On Functionalized Surfacesmentioning
confidence: 99%
“…catalysis [90]. For example, Wan et al reported Al/B doping C2N and g-C3N4 to construct FLPs from their DFT calculations [55].…”
Section: Flps Based On Functionalized Surfacesmentioning
confidence: 99%
“…With the massive consumption of fossil fuels, excessive carbon dioxide (CO 2 ) emissions are considered as a thorny climate and environmental problem. , However, as a reproducible and nontoxic C1 resource, CO 2 can be converted into high-value-added chemicals under certain conditions, realizing the efficient utilization of resources and reducing environment hazards. , The production of cyclic carbonates from CO 2 and epoxide by cycloaddition, as an atom-economic reaction, has attracted a surge of attention. , In view of the large-scale application of cyclic carbonates, homogeneous catalysts and heterogeneous catalysts such as ionic liquids (ILs), metal oxides, metal–organic frameworks (MOFs), zeolites, etc., have been extensively utilized for CO 2 cycloaddition. A homogeneous system is not conducive to product separation . For most heterogeneous catalysts, the toxic metals can be released from metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…With the massive consumption of fossil fuels, excessive carbon dioxide (CO 2 ) emissions are considered as a thorny climate and environmental problem. 1,2 However, as a reproducible and nontoxic C1 resource, CO 2 can be converted into high-valueadded chemicals under certain conditions, realizing the efficient utilization of resources and reducing environment hazards. 3,4 The production of cyclic carbonates from CO 2 and epoxide by cycloaddition, as an atom-economic reaction, has attracted a surge of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al found that the Faraday efficiency for the electrocatalytic reduction of CO 2 to HCOOH can be remarkably enhanced on the single Mo atom loaded N-doped graphene (Mo@NG) compared to N-doped graphene (NG) . In addition, some studies have reported that single-atom Fe-, Co-, or Al-incorporated 2D substrates can also promote CO 2 hydrogenation. However, the main product of CO 2 hydrogenation catalyzed by such SACs is usually HCOOH, while the formation of other C1 products is rarely reported. Herein, a crucial issue then arises: Is there a metal-embedded SAC catalyst that can produce different C1 products of CO 2 hydrogenation such as CH 3 OH?…”
Section: Introductionmentioning
confidence: 99%